Promoting Civil Discourse through Coffee and Common Ground - Alan English (The Advocate, 2023)
Research suggests that America today is more politically polarized and less capable of conducting civil public discourse than at least the last several decades. These greater cultural factors unsurprisingly seem to have trickled into American schools, as teachers report increased divisiveness and conflict, particularly directed toward historically-marginalized groups, in class. While it seems sensible that public schools should play a role in teaching American children how to civilly speak with people different than themselves, teachers are often unprepared to do so. This paper describes a project-based learning activity conducted during the Fall 2022 semester which was designed to empower pre-service teachers with practical tools to promote civil discourse in their future classrooms.
Keywords: Project-based learning; Civil Discourse; Teacher education